2017
DOI: 10.2147/opth.s135461
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy combined with antivascular endothelial growth factor treatment for recalcitrant chronic central serous chorioretinopathy

Abstract: PurposeTo determine whether combination photodynamic therapy (PDT) and antivascular endothelial growth factor (VEGF) therapy is effective in the management of chronic central serous chorioretinopathy (CSC) recalcitrant to conventional therapy.MethodsThis was a retrospective analysis of eight patients with chronic CSC unresponsive to topical nonsteroidal anti-inflammatory drugs, focal photocoagulation, anti-VEGF alone, or PDT alone. All patients were evaluated with a full ophthalmic examination, spectral-domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…The author concluded that IVB injection can be a treatment modality for chronic CSC, which was compatible to our study results. Also, a combination of PDT with IVB injection may be effective in the management of chronic CSC 39, 40, 41. Naseripour et al.…”
Section: Discussionmentioning
confidence: 99%
“…The author concluded that IVB injection can be a treatment modality for chronic CSC, which was compatible to our study results. Also, a combination of PDT with IVB injection may be effective in the management of chronic CSC 39, 40, 41. Naseripour et al.…”
Section: Discussionmentioning
confidence: 99%
“…Existují však jen velmi omezená data dokazující účinnost a bezpečnost kombinované léčby PDT a anti-VEGF. Asahi demonstroval pozitivní výsledky kombinované terapie HD-PDT + aflibercept u pacientů nereagujících na konvenční léčbu (laserfotokoagulace, monoterapie PDT, monoterapie anti-VEGF), větší úspěch zaznamenal především u očí komplikovaných CNV [150].…”
Section: Anti-vegf Terapieunclassified
“…Existují však jen velmi omezená data dokazující účinnost a bezpečnost kombinované léčby PDT a anti-VEGF. Asahi demonstroval pozitivní výsledky kombinované terapie HD-PDT + aflibercept u pacientů nereagujících na konvenční léčbu (laserfotokoagulace, monoterapie PDT, monoterapie anti-VEGF), větší úspěch zaznamenal především u očí komplikovaných CNV [2].…”
Section: Diskuseunclassified